TACTICAL-TECHNICAL ASPECTS AND DEFENSIVE SYSTEMS IN HANDBALL FOR THE U-14 TEAMS: INDICATIONS FOR THE TEACHING PROCESS - de Oliveira Granero, Gustavo (2024)
Tactical-technical aspects and defensive systems in handball constitute specific knowledge which needs to be organized and planned for teaching by the coach. This study identified defensive content and preferences for its teaching among U-14 teams’ coaches. Thirteen coaches of teams participating in the championships of the São Paulo Handball Federation were interviewed, and their statements were analyzed using the Collective Subject Discourse method. The results indicated preferences for defensive systems (man-to-man, 3:3, and 5:1), tactical-technical aspects (marking, floating, coverage, and position exchange), and teaching through games and game situations. It is expected that the results will contribute to expanding discussions on this topic.